The MAP2K5-linked SNP rs2241423 is associated with BMI and obesity in two cohorts of Swedish and Greek children - Rask-Andersen Mathias; Jacobsson Josefin A; Moschonis George; Ek Anna E; Chrousos George P; Marcus Claude; Manios Yannis; Fredriksson Robert; Schiöth Helgi B (BMC, 2012)
Abstract Background Recent genome-wide association studies have identified a single nucleotide polymorphism within the last intron of MAP2K5 associated with a higher body mass index (BMI) in adults. MAP2K5 is a component of the MAPK-family intracellular signaling pathways, responding to extracellular growth factors such as brain derived neurotrophic factor (BDNF) and nerve growth factor (NGF). In this study, we examined the association of this variant in two cohorts of children from Sweden and Greece. Methods We examine the association of rs2241423 to BMI in a cohort of 474 Swedish children admitted for treatment of childhood obesity and 519 children matched for gender, ethnicity and socioeconomic background from the Stockholm area, as well as a cross-sectional cohort of 2308 Greek school children (Healthy Growth Study). Children were genotyped using a predesigned TaqMan polymorphism assay. Logistic regression was used to test for an association of rs2241423 to obesity in the cohort of Swedish children. Linear regression was used to test for an association of rs2241423 to BMI z-score and phenotypic measurements of body adiposity in the cohort of Greek children. Models were adjusted for age and gender. In the cohort of Greek children the model was also adjusted for stage of pubertal development. Results The minor allele of rs2241423, allele A, was associated with a protective effect against obesity in the cohort of Swedish children (p = 0.029, OR = 0.79 (95% CI: 0.64-0.98)), and with a lower BMI z-score in the cohort of Greek children (p = 0.028, β = −0.092). No association to phenotypic measurements of body fat distribution could be observed in our study. Conclusions rs2241423 was associated with BMI and obesity in two independent European cohorts suggesting a role for MAP2K5 in early weight regulation.